Screening and Molecular Characterization of Oleaginous Yeasts and Their Potentiality for Single Cell Oil Production (University of Khartoum Journal of Agricultural Sciences, 2022)
The study aimed to isolate oleaginous yeasts from different sources (rotten fruits, fruit juices, milk, fish and air) and to identify and to study the possibility of production of single cell oil (SCO) from wheat straw and sugarcane molasses media. Thirty samples of yeasts were isolated using different methods according to the source of isolates. The isolated yeasts were characterized using microscopic appearance, colony morphology, physiological tests, assimilation tests and molecular identification. The effectiveness of oleaginous yeast to produce the single cell oil was studied, by growing the yeast on two types of wheat straw media (detoxified liquid hydrolysate (DLH) and non-detoxified liquid hydrolysate (NDLH)), and molasse media. Single cell oil was extracted by hexane. Eighteen isolates were found to be yeast, and the profile of ten yeast samples was identified as Saccharomyces cerevisiae, while, one sample was identified as Pichia guilliermondii. DLH wheat straw gave higher productivity of oil than NDLH wheat straw. Generally, S. cerevisiae gave higher oil productivity (84 %), compared to P. guilliermondii (52 %).
Keywords: Oleaginous yeast; Saccharomyces cerevisiae; Pichia guilliermondii; single cell oil